Marketing and higher education: Condition in Serbia - Marković Saša; Vujović Slavoljub; Damnjanović Aleksandar (Ekonomika Poljoprivrede (1979), 2017)
The inductive research approach is directed to testing of the hypothesis: about implementing marketing management, depending on the configuration properties of a successful education, and expressed with increased customer satisfaction in Serbia. The survey results confirm that the quality of service in higher education institutions in Serbia depends on the configuration properties of a successful education. Finally, it was confirmed that the success of marketing activities directly depends on the degree of customer satisfaction. One of the main specificities of higher education, even in comparison to other industries and service, is that the service provides a number of years and what is its value after successful completion of use, lifetime. Higher education institutions are in a unique position to build good relations with existing customers directly affected by the increase in the number of users in the future tense.